# Cosmology

posted by .

The equation describing the geometry and mass-energy distribution of a homogeneous and isotropic universe is known as:

- The Einstein Equation
- The Friedmann Equation
- The Robertson-Walker Equation
- The Hubble Equation

## Similar Questions

1. ### einstein's equation

Einstein's famous equation indicates that E=mc^2, where c is the speed of light and m is the object's mass. Given this, what is the SI unit for E?
2. ### MATH

I NEED TO SOLVE FOR Y AND X im getting rele confused on this. ok here is the prob. x+y=5 x-2y=-4 equation 1 x+y=5 equation 2 x-2y=-4 Multiply equation 1 by -1. Add equation 1 to equation 2. The x term cancels. Solve for y. THEN, put …
3. ### Cosmology

A curvature constant of k=0, as used in the Friedmann equation, means: * The universe is open * The universe is matter-dominated * There is no dark energy * The universe is flat
4. ### physics

Which equation would you use when you were describing a flowing viscous fluid?
5. ### Chemistry

For the following equation, write a thermochemical equation that includes an energy term within the equation: The formation of 1 mol of copper(II)chloride from its elements releases 220.1kJ of energy.
6. ### ALGEBRA

The table below shows two equations: Equation 1 |3x - 1| + 7 = 2 Equation 2 |2x + 1| + 4 = 3 Which statement is true about the solution to the two equations?
7. ### math

compare and contrast: below are two equations. solve each equation and compare the two solutions. choose the statement that is true about each solution. equation #1 2x-3=-17 5x+3=12 A. equation #1 and equation #2 have the same number …
8. ### physics

in einstein's famous equation e=mc^2, describing the relationship between matter and energy, the units for E are m=====>kg, c=====>m/s a) kg m/s b)kg m/s^2 c) m^2/s^2 d)kg m^2/s^2 I think its either B or D but indecisive...
9. ### Science

Einstein put forward the mass-energy equation E=mc2. Can anybody explain why c is squared(2)?
10. ### Math

A student is trying to solve the set of two equations given below: Equation A: x + z = 6 Equation B: 2x + 4z = 1 Which of the following is a possible step used in eliminating the z-term?

More Similar Questions